Transformational Leadership and Innovation Work Behavior: The Role of Perceived Organizational Support and Knowledge Sharing - NaNa, Liu; Zainal, Siti Rohaida Binti Mohamed (Journal of Ecohumanism, 2024)
The relationship between transformational leadership and innovation behavior is pivotal in enhancing organizational performance and competitiveness. This study explores how perceived organizational support and knowledge sharing mediate this relationship. Transformational leadership inspires employees to pursue innovation by fostering an environment where creativity thrives. However, this relationship is strengthened when employees perceive strong organizational support, as they feel valued and encouraged to engage in innovative behaviors. Additionally, knowledge sharing among employees plays a crucial role, as it facilitates the exchange of ideas and expertise necessary for innovation. By examining these mediators, the study highlights how organizational culture and leadership practices can be aligned to maximize innovative outcomes. Data were collected from IT of large- and mid-sized companies in China. Survey data from 367 team members were tested using PLS-SEM modeling analysis. The findings suggest that for transformational leadership to effectively drive innovation, organizations must actively support their employees and promote a culture of open knowledge sharing.